2022
DOI: 10.1039/d1ra07336b
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential biological activities of TiO2 and Cu, Ni and Cr doped TiO2 nanoparticles

Abstract: Nanoparticles bind to the surface of the cell membranes of microbes altering their basic cell functions and resulting in cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…These nanocomposites are commonly employed as nano delivery systems that improve bioavailability, biodistribution, and preferentially localizing diseased tissues while protecting healthy tissues. However, because of their chemical nature, many metal ion (TiO 2 /CuO) based nanoparticles also demonstrate effective antibacterial activity [ 30 , 31 ]. The antibacterial potential of a Berberis vulgaris plant extract against microorganisms linked with caries, such as Streptococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…These nanocomposites are commonly employed as nano delivery systems that improve bioavailability, biodistribution, and preferentially localizing diseased tissues while protecting healthy tissues. However, because of their chemical nature, many metal ion (TiO 2 /CuO) based nanoparticles also demonstrate effective antibacterial activity [ 30 , 31 ]. The antibacterial potential of a Berberis vulgaris plant extract against microorganisms linked with caries, such as Streptococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, they can also interfere with essential cellular functions, leading to cell death and affecting cell division and protein synthesis. In a different study, Matras and colleagues [200] found Ag-NPs potent antifungal properties in in vitro experiments on F. avenaceum and F. equiseti by disrupting the cell membrane structure, hindering budding activity, and preventing cytotoxicity. Munir and his research group [201] found that titanium ions permeate cell membranes and bind with DNA, while Cu-, Cr-, and Ni-doped TiO2 binds to fungal cells, enhancing its antifungal activity.…”
Section: Mode Of Action Of Nms For Antifungal Activitymentioning
confidence: 99%
“…In a different study, Matras and colleagues [199] found Ag-NPs potent antifungal properties in in vitro experiments on F. avenaceum and F. equiseti by disrupting the cell membrane structure, hindering budding activity, and preventing cytotoxicity. Munir and his research group [200] found that titanium ions permeate cell membranes and bind with DNA, while Cu-, Cr-, and Ni-doped TiO 2 binds to fungal cells, enhancing its antifungal activity. Accordingly, Morsy and colleagues [201] discovered that CuO-NPs significantly impact broiler chickens growth, immune status, DNA status, and histological structures, with dose-dependent increases in malondialdehyde levels, Cu contents, and the DNA fragmentation percent.…”
Section: Mode Of Action Of Nms For Antifungal Activitymentioning
confidence: 99%